Smart Farming System on Red Onion Plants Based on the Internet of Things - Hadi, Sirojul; Cahyati, Anzali Ika; Latif, Kurniadin Abd; Sujaka, Tomi Tri; Zulfikri, Muhammad (Sistemasi: Jurnal Sistem Informasi, 2023)
Red Onions are agricultural commodities that are a source of income for farmers and can make a major contribution to Indonesia's economic development. The characteristic of the onion plant is that it requires a lot of sunlight. The sunlight needed for photosynthesis is 70% with an ambient temperature range of 25oC-32oC and soil moisture in the range of 50%-70%. Although red onions require a lot of water, these plants are sensitive to high-intensity rainfall. The critical period of the red onion plants is in the tuber formation phase so it is necessary to control it to get maximum production results. The method of making the smart farming system uses the Research and Development (R&D) method while sending data online to the web uses the Internet of Things (IoT) method. The result of this research is that a monitoring and control system for temperature and humidity has been successfully built on red onion plants. The system built is capable of measuring temperature with an accuracy rate of 95.33% and environmental humidity in plants reaching 92.07% while the accuracy of testing the entire system reaches 93.33%. The smart farming system has been able to automatically irrigate and apply fertilizer. Control of irrigation and application of fertilizers by the system has implications for better shallot growth and creates modern agriculture.